USM TO HOST PUBLIC LECTURE BY PAKISTAN HIGH COMMISSIONER TO MALAYSIA SYED HASSAN RAZA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 5 November 2016 – The High Commissioner of Islamic Republic of Pakistan to Malaysia, HE Syed Hassan Raza will give a public talk entitled ‘Economic Development and CPEC Cooperation between Pakistan and China: Opportunities for other Countries’ on Tuesday, 8 November 2016, beginning at 2.30 p.m. in the Dewan Persidangan Universiti (DPU), Universiti Sains Malaysia (USM).